Challenges and Enablers to Smoking Cessation for Young Pregnant Australian Women: A Qualitative Study - Hauck, Yvonne; Ronchi, F.; Lourey, B.; Lewis, Lucy (Blackwell Publishers, 2013)
BACKGROUND: Western Australian (WA) perinatal statistics indicate an 8 percent decrease in smoking by pregnant women from 1999 to 2009. Despite the success of cessation interventions, the incidence of tobacco smokers among young pregnant women remains a cause for concern. To inform development of an appropriate suite of interventions, a qualitative study was undertaken to gain insight into the perceived challenges and enablers young pregnant women encounter when attempting to modify their smoking.METHOD: A hypothetical scenario and interview questions were used: if a young pregnant woman decided to decrease or stop her smoking 1) what could assist her, and 2) what are the challenges that she would need to overcome? Thematic analysis was conducted. Our sample included English-speaking pregnant women recorded as a smoker, 16 to 24 years of age, and attending antenatal services at a public maternity hospital.RESULTS: Thirty-six women participated in an interview. “Habit” was noted as the key theme under perceived challenges and incorporated three subthemes: learn to deal with stress; the urge for a smoke; and not being left out. Concern over the health of their baby emerged as the main theme and enabler to change behavior. Four subthemes were extracted around keeping their baby healthy: getting the facts; you need someone; something you can take to help; and keeping your mind off it.CONCLUSIONS: Our findings highlight the complex issues around smoking for young pregnant WA women. Insight into these challenges and enablers may inform development of more suitable interventions to address the unique needs of this group of pregnant women.